Evidence Review of the Adverse Effects of COVID-19 Vaccination and Intramuscular Vaccine Administration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Vaccines are a public health success story, as they have prevented or lessened the effects of many infectious diseases. To address concerns around potential vaccine injuries, the Health Resources and Services Administration (HRSA) administers the Vaccine Injury Compensation Program (VICP) and the Countermeasures Injury Compensation Program (CICP), which provide compensation to those who assert that they were injured by routine vaccines or medical countermeasures, respectively. The National Academies of Sciences, Engineering, and Medicine have contributed to the scientific basis for VICP compensation decisions for decades. HRSA asked the National Academies to convene an expert committee to review the epidemiological, clinical, and biological evidence about the relationship between COVID-19 vaccines and specific adverse events, as well as intramuscular administration of vaccines and shoulder injuries. This report outlines the committee findings and conclusions.
Keywords: Health and Medicine

Decarcerating Correctional Facilities during COVID-19: Advancing Health, Equity, and Safety - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The conditions and characteristics of correctional facilities - overcrowded with rapid population turnover, often in old and poorly ventilated structures, a spatially concentrated pattern of releases and admissions in low-income communities of color, and a health care system that is siloed from community public health - accelerates transmission of the novel coronavirus (SARS-CoV-2) responsible for COVID-19. Such conditions increase the risk of coming into contact with the virus for incarcerated people, correctional staff, and their families and communities. Relative to the general public, moreover, incarcerated individuals have a higher prevalence of chronic health conditions such as asthma, hypertension, and cardiovascular disease, making them susceptible to complications should they become infected. Indeed, cumulative COVID-19 case rates among incarcerated people and correctional staff have grown steadily higher than case rates in the general population. Decarcerating Correctional Facilities during COVID-19 offers guidance on efforts to decarcerate, or reduce the incarcerated population, as a response to COIVD-19 pandemic. This report examines best practices for implementing decarceration as a response to the pandemic and the conditions that support safe and successful reentry of those decarcerated.
Keywords: Behavioral and Social Sciences; Health and Medicine

Rapid Expert Consultation on Critical Federal Capabilities Needed to Evaluate Real-World Safety, Effectiveness, and Equitable Distribution and Use of Medical Countermeasures During a Public Health Emergency - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The COVID-19 pandemic has highlighted the importance of having access to real-world data and evidence to monitor and assess medical countermeasure (MCM) use and performance so policy makers can make more effective and rapid public health decisions, protect population health, and save lives. During public health emergencies, the use of MCMs, such as therapeutics, vaccines, and diagnostics, can be made available to the public under a range of regulatory access mechanisms. This Rapid Expert Consultation was produced by individual members of the Standing Committee for CDC Center for Preparedness and Response. Its aim is to review and propose modifications to an initial draft list of critical federal capabilities presented by the Centers for Disease Control and Prevention and the U.S. Food and Drug Administration that are needed to evaluate real-world safety, effectiveness, equitable distribution, access, and use of MCMs during a public health emergency. This effort draws from expert input, published literature, and lessons learned from previous public health emergencies, as well as the ongoing COVID-19 pandemic.
Keywords: Health and Medicine

Exploring Lessons Learned from Partnerships to Improve Global Health and Safety: Workshop in Brief - Institute of Medicine (The National Academies Press, 2015)
Drawing on relevant perspectives from both the private and public sectors, the Forum on Public–Private Partnerships for Global Health and Safety (PPP Forum) held a workshop on November 18–19, 2014, to explore motivations, challenges, and lessons learned during four stages of partnerships: engagement, formation, operations, and knowledge management. Workshop objectives were to engage in forward-looking multisectoral dialogue on the evolving models of partnerships for improving global health and safety; to explore opportunities for identifying and applying lessons learned from experiences of success and failure; and to discuss how the evolving model of partnerships and lessons learned can impact the future state of global health and safety, help meet global developmental challenges, and sustain improved outcomes. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Emergency Evacuation and Sheltering During the COVID-19 Pandemic - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Fundamental shifts in preparedness planning are needed to ensure health, safety, and smooth operations during emergencies in the context of the COVID-19 pandemic. To prepare for emergency events requiring evacuation, it is necessary to revise shelter planning and mass care operations, shelter staffing, and shelter design and operations with a focus on reducing virus transmission and ensuring safety. Developing effective public messaging is also critical during the pandemic and requires advance planning and familiarity with the needs and characteristics of the communities being served. This rapid expert consultation details what is known from research on evacuation behavior, social responses to disaster, and risk communication, as well as lessons learned from emergency managers, public health departments, local officials, and human service providers, as the second year of the pandemic unfolds. It includes strategies for (1) evacuation plans, (2) sheltering operations, and (3) risk communication best practices for public officials confronting hazards and disasters. The Societal Experts Action Network (SEAN) is an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats.
Keywords: Health and Medicine

Addressing Disaster Vulnerability among Homeless Populations during COVID-19 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
During the COVID-19 pandemic, disruptions to key services for populations experiencing homelessness may lead to secondary effects in the context of a disaster, including effects on health and safety, which require additional population-specific support. Reducing disaster vulnerability for people experiencing homelessness during the COVID-19 pandemic requires adapting existing preparedness guidance to an evolving situation. Addressing Disaster Vulnerability among Homeless Populations during COVID-19 reviews research on disaster vulnerability, homelessness, the pandemic, and intersecting hazards and disasters. This rapid expert consultation includes considerations for alternative shelter facilities for homeless populations during a disaster; suggestions on how to navigate service reductions and support population-specific needs; and guidance for supporting populations experiencing homelessness in the aftermath of disasters. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation and the Alfred P. Sloan Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats, sponsored by the U.S. Department of Health and Human Services, Office of the Assistant Secretary for Preparedness and Response.
Keywords: Behavioral and Social Sciences

Stronger Food and Drug Regulatory Systems Abroad - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Ensuring the safety of food and the quality and safety of medicines in a country is an important role of government, made more complicated by global manufacturing and international trade. By recent estimates, unsafe food kills over 400,000 people a year, a third of them children under 5, mostly in low- and middle-income countries; every year poor quality medicines cause about 70,000 excess deaths from childhood pneumonia and roughly 8,500 to 20,000 malaria deaths in sub-Saharan Africa alone. The Federal Drug Administration (FDA) Office of Global Policy and Strategy is charged with improving capacity of the agency's foreign counterpart offices and increasing understanding of the importance of regulatory systems for public health, development, and trade. At the request of the FDA, this study sets out a strategy to support good quality, wholesome food and safe, effective medical products around the world. Its goal is to build on the momentum for strengthening regulatory systems and to set a course for sustainability and continued progress. The 2012 report Ensuring Safe Food and Medical Products Through Stronger Regulatory Systems Abroad outlined strategies to secure international supply chains, emphasized capacity building and support for surveillance in low- and middle-income countries, and explored ways to facilitate work sharing among food and medical product regulatory agencies. This new study assess progress made and the current regulatory landscape.
Keywords: Food and Nutrition; Health and Medicine

Exploring the Role of Health Professional Students and Trainees as Members of the Health Workforce During Crises: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The onset of COVID-19 pandemic and inundation of the U.S. health care system emphasized infrastructural and health professional education vulnerabilities. A planning committee of the National Academies of Sciences, Engineering, and Medicine Global Forum on Innovation in Health Professional Education conducted a series of public workshops in the fall of 2021 to explore whether students and trainees should be viewed as members of the health workforce, particular in times of emergency as was experienced during the COVID-19 public health crisis. The planning committee gathered educators, students, administrators, and health professionals to share ideas, experiences, and data to strategize expansion of learning opportunities for medical trainees and enhancement of medical preparedness to unforeseen crises without compromising the quality of patient care. The workshops explored issues such as identifying evidence on value-added roles for students to serve in the delivery of care and in a public health capacity, and balancing the role of learners as consumers (tuition payers) and not licensed providers versus members of the health workforce. This Proceedings highlights presentations and discussions from the workshop.
Keywords: Health and Medicine

COVID-19 Addendum to Critical Issues in Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The year 2020’s raging coronavirus pandemic and reckoning with long-standing racial injustice led to widespread disruption and suffering, social unrest, and renewed calls for an accounting of our fragmented public health system and troubled history of racial inequity.The crises of 2020 transcend transportation yet also raise fundamental questions for it along with other sectors of our society and economy. In this addendum to Critical Issues in Transportation 2019, the Transportation Research Board (TRB) Executive Committee updates all of the critical issue topic areas to address the short-term and potential long-term effects of coronavirus disease 2019 (COVID-19) on transportation.An additional addendum will be issued later in 2021 that delves much more deeply into the equity issue to probe and question transportation’s role in contributing to and redressing racial injustice.
Keywords: Transportation and Infrastructure

The Use and Effectiveness of Powered Air Purifying Respirators in Health Care: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Protecting 18 million United States health care workers from infectious agents - known and unknown - involves a range of occupational safety and health measures that include identifying and using appropriate protective equipment. The 2009 H1N1 influenza pandemic and the 2014 Ebola virus outbreak in West Africa have called raised questions about how best to ensure appropriate and effective use of different kinds of personal protective equipment such as respirators, not only to promote occupational safety but also to reduce disease transmission. The Use and Effectiveness of Powered Air Purifying Respirators in Health Care is the summary of a workshop convened by the Institute of Medicine Standing Committee on Personal Protective Equipment for Workplace Safety and Health to explore the current state of practices and research related to powered air purifying respirator (PAPRs) and potential updates to performance requirements. Presentations and discussions highlighted current health care practices using PAPRs and outlined the research to date on the use and effectiveness of PAPRs in health care settings with a focus on the performance requirements. The Use and Effectiveness of Powered Air Purifying Respirators in Health Care focuses on efficacy, current training, maintenance, supplies, and possible enhancements and barriers to use in inpatient, clinic, nursing home, and community (home) settings. This report also explores the strengths and weaknesses of using various approaches to health care PAPR standards.
Keywords: Health and Medicine

Building a National Capability to Monitor and Assess Medical Countermeasure Use During a Public Health Emergency: Going Beyond the Last Mile: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
During public health emergencies (PHEs) involving chemical, biological, radiological, or nuclear threats or emerging infectious diseases, medical countermeasures (MCMs) (e.g., drugs, vaccines, devices) may need to be dispensed or administered to affected populations to help mitigate the human health impact of the threat. The optimal MCMs determined for use during an emergency might be U.S. Food and Drug Administration (FDA) approved but used in unapproved ways (e.g., in a new age group or against a new agent); FDA approved using animal models because human efficacy testing is not ethical or feasible; or not yet FDA approved for any indication. As part of the United States' scientific and research preparedness enterprise, there is an imperative to go "beyond the last mile" of MCM dispensing and administration to build and maintain a national capability to monitor and assess the use of MCMs (e.g., safety, compliance, clinical benefit) after they have been dispensed during PHEs. To further the discussion on this need, the Board on Health Sciences Policy of the National Academies of Sciences, Engineering, and Medicine hosted a 2-day public workshop, Building a National Capability to Monitor and Assess Medical Countermeasure Use in Response to Public Health Emergencies. The workshop, sponsored by FDA, was held on June 6–7, 2017, in Washington, DC. Workshop participants discussed the roles and efforts of the federal government and of relevant stakeholders with an interest in building and maintaining a national PHE MCM active monitoring and assessment capability. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Reusable Elastomeric Respirators in Health Care: Considerations for Routine and Surge Use - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Protecting the health and safety of health care workers is vital to the health of each of us. Preparing for and responding to a future influenza pandemic or to a sustained outbreak of an airborne transmissible disease requires a high-level commitment to respiratory protection for health care workers across the wide range of settings in which they work and the jobs that they perform. Keeping health care workers healthy is an ethical commitment both in terms of addressing the occupational risks faced by health care workers and of providing for the continuity of patient care and services needed to maintain the health of individuals and communities. During a public health emergency, challenges will arise concerning the availability of respiratory protective devices (i.e., respirators). Reusable respirators (specifically, reusable half-facepiece elastomeric respirators) are the standard respiratory protection device used in many industries, and they provide an option for use in health care that has to date not been fully explored. The durability and reusability of elastomeric respirators make them desirable for stockpiling for emergencies, where the need for large volumes of respirators can be anticipated. However, they are used infrequently in health care. Reusable Elastomeric Respirators in Health Care explores the potential for the use of elastomeric respirators in the U.S. health care system with a focus on the economic, policy, and implementation challenges and opportunities. This report examines the practicability of elastomeric use in health care on a routine basis and during an influenza pandemic or other large aerosol-transmissible outbreak, when demand for respiratory protective devices by U.S. health care personnel may be larger than domestic supplies. The report also addresses the issues regarding emergency stockpile management of elastomeric respiratory protective devices.
Keywords: Health and Medicine

Rapid Response by Laboratory Animal Research Institutions During the COVID-19 Pandemic: Lessons Learned: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The National Academies of Sciences, Engineering, and Medicine convened a workshop to explore lessons learned at animal research institutions in response to SARS-CoV-2, the cause of the COVID-19 pandemic. Expert scientists conducting COVID-19 research, as well as institutional leadership responsible for oversight in areas such as, veterinary medical care, occupational health, risk assessment and biosafety, and public messaging and communications presented and participated in panel discussions. This publication summarizes the presentations and discussion of the workshop.
Keywords: Biology and Life Sciences

Emerging Stronger from COVID-19: Priorities for Health System Transformation - National Academy of Medicine (The National Academies Press, 2023)
In mid-2022, the United States has lost more than 1 million people to the COVID-19 pandemic. We have been real-time witnesses to scores of heroic responses to the disease, death, inequity, and economic strife unleashed by the virus, but have also experienced the consequences of poor pandemic preparedness and long-standing structural failures in our health system. For decades, the U.S. health system has fallen far short of its potential to support and improve individual and population health. The COVID-19 pandemic has presented death and devastation—but also an unprecedented opportunity to truly transform U.S. health, health care, and health delivery. To capitalize on this opportunity, the National Academy of Medicine gathered field leaders from across all of the major health system sectors to assess how each sector has responded to the pandemic and the opportunities that exist for health system transformation. The opportunity is now to capitalize on the hard-won lessons of COVID-19 and build a health care system that centers patients, families, and communities; cares for clinicians; supports care systems, public health, and biomedical research to perform at the best of their abilities; applies innovations from digital health and quality, safety, and standards organizations; and encourages health care payers and health product manufacturers and innovators to produce products that benefit all.
Keywords: Health and Medicine

Addressing the Impact of COVID-19 on the Early Care and Education Sector - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The COVID-19 pandemic has exacerbated challenges in the early care and education (ECE) sector, including: preexisting structural flaws; insufficient funding mechanisms; sector fragmentation; inadequate support for the workforce; and inequalities, such as the lack of access to high-quality care among low-income, rural populations, and communities of color. Addressing the impacts of the pandemic and the resulting economic recession on the ECE sector will require that state, local, and tribal decision makers use available COVID-19 relief funds to mitigate those impacts while also laying the foundation for longer-term solutions. This rapid expert consultation identifies mitigation strategies that could be implemented to achieve these goals. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation and the Alfred P. Sloan Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats. The National Bureau of Economic Research with the support of the Alfred P. Sloan Foundation commissioned the white papers that informed the development of this rapid expert consultation.
Keywords: Education

The Food and Drug Administration's Emergency Use Authorization: Lessons Learned from the Past to Guide the Future: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The U.S. Food and Drug Administration (FDA) has responsibility for protecting public health by ensuring the safety, efficacy, and security of drugs, biological products, and medical devices. In certain declared emergencies, FDA has the option to authorize use of a new product or a new use of an approved product - an authority known as Emergency Use Authorization (EUA)- if it has reason to believe that the product may be effective and that its known benefits outweigh its known risks. By contrast, in non-emergency situations, applicants must demonstrate a product's safety and effectiveness through a lengthier, more extensive process. On October 5-6, 2021, the Committee on Science, Technology, and Law of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on the EUA process. At the workshop, presenters and participants examined FDA's recent and historic use of EUAs, discussed lessons learned during the COVID-19 pandemic, and considered how those lessons might inform future efforts. The workshop also highlighted emergency mechanisms used by other health regulators and considered how U.S. and global regulatory partners can strengthen cooperation in responding to global health emergencies. This publication summarizes the presentation and discussion of the workshop.
Keywords: Policy for Science and Technology

International Workshop on COVID-19 Lessons to Inform Pandemic Influenza Response: Proceedings of a Workshop - National Academy of Medicine (The National Academies Press, 2022)
While the world continues to respond to the COVID-19 pandemic, novel influenza viruses persist as a constant pandemic threat. The global response to COVID-19 has pushed the boundaries on what is possible for rapid pandemic response in several areas, including vaccine research, development, manufacturing, equitable distribution, allocation, and administration. If well understood and sufficiently adapted, these actions could be applied to future pandemic and seasonal influenza vaccine preparedness efforts. However, developing and delivering these more effective vaccines to meet the demand goes beyond simply technical challenges and includes issues across governance, financing, research, supply chain, and public engagement. To address these challenges, the National Academies of Sciences, Engineering, and Medicine convened a virtual public workshop in May of 2021 to discuss the emerging evidence on unprecedented actions related to COVID-19 that could inform and advance pandemic and seasonal influenza vaccine preparedness efforts and subsequent response. This Proceedings of a Workshop provides a high-level summary of the presentations and discussions that occurred during the workshop.
Keywords: Health and Medicine

Respiratory Protection for Healthcare Workers in the Workplace Against Novel H1N1 Influenza A: A Letter Report - Institute of Medicine (The National Academies Press, 2009)
In the event that the H1N1 virus creates a surge of patients during the upcoming flu season, it will be critical to protect health care workers from infection, given their central role in treating sick people and lessening the pandemic's overall impact. This new report from the Institute of Medicine recommends strategies for health care organizations and employees to prepare for the H1N1 virus. These recommendations include wearing fitted N95 respirators to guard against respiratory infection by the virus, and establishing policies for innovative triage processes, handwashing, disinfection, and more. The report also calls for a boost in research to answer questions about how the flu viruses can be spread, and to design and develop better protective equipment that would enhance workers' comfort, safety, and ability to do their jobs.
Keywords: Health and Medicine

Applying Lessons Learned from COVID-19 Research and Development to Future Epidemics: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The COVID-19 pandemic catalyzed unparalleled speed and cross-sector collaboration in the innovation of tools and technologies to address an emerging infectious disease outbreak. Continued innovation and collaboration in rapid development and implementation of new vaccines, therapeutics, and diagnostics is central to future outbreak preparedness. The National Academies Forum on Microbial Threats; Forum on Drug Discovery, Development, and Translation; and the Forum on Medical and Public Health Preparedness for Emergencies and Disasters held a workshop in December 2022 to explore how innovative approaches in research can enhance health systems preparedness and responses to emerging infectious diseases and dangerous pathogens. Workshop participants reflected on critical scientific infrastructure for stakeholder coordination and innovations that can facilitate rapid and effective preparedness and response to emerging infectious disease threats. This Proceedings of a Workshop summarizes the discussions held during the workshop.
Keywords: Health and Medicine

Evidence-Based Practice for Public Health Emergency Preparedness and Response - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
When communities face complex public health emergencies, state local, tribal, and territorial public health agencies must make difficult decisions regarding how to effectively respond. The public health emergency preparedness and response (PHEPR) system, with its multifaceted mission to prevent, protect against, quickly respond to, and recover from public health emergencies, is inherently complex and encompasses policies, organizations, and programs. Since the events of September 11, 2001, the United States has invested billions of dollars and immeasurable amounts of human capital to develop and enhance public health emergency preparedness and infrastructure to respond to a wide range of public health threats, including infectious diseases, natural disasters, and chemical, biological, radiological, and nuclear events. Despite the investments in research and the growing body of empirical literature on a range of preparedness and response capabilities and functions, there has been no national-level, comprehensive review and grading of evidence for public health emergency preparedness and response practices comparable to those utilized in medicine and other public health fields. Evidence-Based Practice for Public Health Emergency Preparedness and Response reviews the state of the evidence on PHEPR practices and the improvements necessary to move the field forward and to strengthen the PHEPR system. This publication evaluates PHEPR evidence to understand the balance of benefits and harms of PHEPR practices, with a focus on four main areas of PHEPR: engagement with and training of community-based partners to improve the outcomes of at-risk populations after public health emergencies; activation of a public health emergency operations center; communication of public health alerts and guidance to technical audiences during a public health emergency; and implementation of quarantine to reduce the spread of contagious illness.
Keywords: Health and Medicine